2007
DOI: 10.1371/journal.pone.0001311
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Open-Label Trial of Artesunate- Sulfadoxine-Pyrimethamine with or without Primaquine for Elimination of Sub-Microscopic P. falciparum Parasitaemia and Gametocyte Carriage in Eastern Sudan

Abstract: BackgroundIn areas of seasonal malaria transmission, treatment of asymptomatic carriers of malaria parasites, whose parasitaemia persists at low densities throughout the dry season, could be a useful strategy for malaria control. We carried out a randomized trial to compare two drug regimens for clearance of parasitaemia in order to identify the optimum regimen for use in mass drug administration in the dry season.Methodology and Principal FindingsA two-arm open-label randomized controlled trial was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 33 publications
1
60
1
Order By: Relevance
“…This addition reduced gametocyte prevalence during treatment and the risk of transmission to another host. These results are in contrast to those reported by El-Sayed and others 19 who concluded that adding PQ did not reduce sexual and asexual parasitemias. These results may be partly explained by the fact that PQ was added to treatment with AS + SP on the fourth day after starting treatment, and treatment was evaluated for asymptomatic patients who had been diagnosed as having submicroscopic parasitemia by polymerase chain reaction.…”
Section: Discussioncontrasting
confidence: 99%
“…This addition reduced gametocyte prevalence during treatment and the risk of transmission to another host. These results are in contrast to those reported by El-Sayed and others 19 who concluded that adding PQ did not reduce sexual and asexual parasitemias. These results may be partly explained by the fact that PQ was added to treatment with AS + SP on the fourth day after starting treatment, and treatment was evaluated for asymptomatic patients who had been diagnosed as having submicroscopic parasitemia by polymerase chain reaction.…”
Section: Discussioncontrasting
confidence: 99%
“…On the contrary, studies from Sudan and India showed reduced or no effect of PQ [29] [30]. These studies agree with Okell et al, who in a randomized controlled study also showed conclusively that a six-dose course of Artemether-Lumefantrine (co-artemether) given to children with P. falciparum malaria in Gambia reduces gametocyte prevalence, duration of gametocyte carriage, and infectiousness to mosquitoes [31].…”
Section: Discussionsupporting
confidence: 76%
“…Additionally, most studies attest to the considerable contribution of sub-microscopic gametocytaemia to mosquito infection [30] [32]. Measuring the effects of the different treatments on submicroscopic gametocytaemia using molecular methods of gametocyte detection such as the PCR would have increased the power of the study since microscopy notoriously underestimates gametocytes counts [30].…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Finally, with lower levels of transmission, acquired immunity is expected to be lower. So at any given time point, an individual may be more likely to be asymptomatic because he/she is either in the process of resolving parasitemia due to treatment or might be in the process of developing a symptomatic infection [7,4,24,25]. Each of these major differences means that the asymptomatic reservoir may vary in different settings with regards to persistence, gametocyte carriage, and hence mosquito infectivity and transmission potential.…”
Section: The Asymptomatic Reservoir Is Heterogeneous In Terms Of Persmentioning
confidence: 99%